A PROSPECTIVE STUDY OF ELECTROLYTE IMBALANCE AND ITS MANAGEMENT IN GASTROINTESTINAL SURGERY - Yadav, Vijay Kumar; Salim, Mohammed; Sharma, Sanjay; Kumar, Rohan (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective is to study electrolyte imbalance and its management in gastrointestinal (GI) surgery. Methods: The present study was carried out in the Department of Surgery, S.P. Medical College and P.B.M Hospital, Bikaner. This is a prospective descriptive study and was carried out between December 2021 and November 2022 including 100 cases operated for GI tract surgeries (both elective and emergency). Results: Out of 100 patients, 54% patient had electrolyte imbalance and required correction for same. 46% of patients had normal serum electrolytes post-operatively. The most common electrolyte imbalance observed is hyponatremia (30%) followed by both hypokalemia and hyponatremia (14%). We observed that the most common surgical interventions which had electrolyte imbalance were ileostomy patients (84%) followed by resection and anastomosis of bowel (70%). Conclusion: Patients who had electrolyte imbalance were found to have more post-operative complications, longer hospital stay, and probably had an association with mortality. Early diagnosis, aggressive resuscitation, and timely definitive surgical treatment along with correction of electrolyte imbalance are essential to decrease the incidence of morbidity and mortality associated with electrolyte imbalance.